Caffeic Acid Versus Caffeic Acid Phenethyl Ester in the Treatment of Breast Cancer MCF-7 Cells: Migration Rate Inhibition - Agata Kabała-Dzik PhD; Anna Rzepecka-Stojko PhD; Robert Kubina PhD; Robert Dariusz Wojtyczka PhD; Ewa Buszman PhD; Jerzy Stojko PhD (Integrative Cancer Therapies, 2018)
Epithelium mammary carcinoma is a cancer with a high death rate among women. One factor having a significant impact on metastasis is cell migration. The aim of this study was to compare migration rate inhibition of caffeic acid (CA) and its phenethyl ester (CAPE) on MCF-7 breast cancer cells. Microscopic evaluation was used to determine the morphology of carcinoma cells, before and after 24-hour treatment with CA and CAPE using a dose of 50 µM. The cytotoxic effect was measured by XTT-NR-SRB assay (tetrazolium hydroxide-neutral red-Sulforhodamine B) for 24-hour and 48-hour periods, using CA and CAPE, with doses of 50 and 100 µM. These doses were used to determine cell migration inhibition using a wound closure assay for 0-hour, 8-hour, 16-hour, and 24-hour periods. Both CA and CAPE treatments displayed cytotoxic activity in a dose- and time-dependent trend. CAPE displayed IC 50 values more than twice as low as CA. IC 50 values for the XTT assay were as follows: CA was 102.98 µM for 24 hours and 59.12 µM for 48 hours, while CAPE was 56.39 µM for 24 hours and 28.10 µM for 48 hours. For the NR assay: CA was 84.87 µM at 24 hours and 65.05 µM at 48 hours, while CAPE was 69.05 µM at 24 hours and 29.05 µM at 48 hours. For the SRB assay: At 24 hours, CA was 83.47 µM and 53.46 µM at 48 hours, while CAPE was 38.53 µM at 24 hours and 20.15 µM at 48 hours. Both polyphenols induced migration inhibition, resulting in practically halting the wound closure. CAPE produced better results than CA with the same doses and experiment times, though both CA and CAPE displayed cytotoxic activity against MCF-7 cells, as well as inhibited migration.